2013
DOI: 10.1007/s13191-013-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Surface Roughness in Dental Ceramics Submitted to Different Finishing and Polishing Methods

Abstract: Ceramic restorations have been widely used in dentistry. These restorations often require intraoral adjustment with diamond burs after their cementation causing increasing roughness of the ceramic surface. Consequently some finishing and polishing methods have been used to minimize this occurrence. The aim of this study is to evaluate the roughness of the ceramic surfaces submitted to different finishing and polishing methods. 144 specimens of VITAVM(®)7, VM(®)9 and VM(®)13 (VITA Zahnfabrik) ceramics were fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 15 publications
5
21
0
12
Order By: Relevance
“…The veneered zirconia groups (i.e., conventional, pressed, digital) followed a similar pattern in the reduction of the surface roughness; however, the level of surface roughness was still significantly higher than the glazed surface even after all finishing and polishing steps were completed. Similar to the present findings, a previous study compared the surface roughness of Vita VM7, VM9, and VM13 after finishing and polishing with a Shofu kit . The authors concluded that finishing and polishing procedures were not able to produce a surface as smooth as the glazed surface.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The veneered zirconia groups (i.e., conventional, pressed, digital) followed a similar pattern in the reduction of the surface roughness; however, the level of surface roughness was still significantly higher than the glazed surface even after all finishing and polishing steps were completed. Similar to the present findings, a previous study compared the surface roughness of Vita VM7, VM9, and VM13 after finishing and polishing with a Shofu kit . The authors concluded that finishing and polishing procedures were not able to produce a surface as smooth as the glazed surface.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were reported for monolithic and opaque zirconia . On the other hand, other studies reported that glazing is the best procedure for obtaining surface smoothness . Also, feldspathic porcelain was reported to have higher surface roughness than zirconia after finishing and polishing procedures …”
supporting
confidence: 82%
“…The glazed groups had a much lower surface roughness than the polished groups, consistent with previous reports . This is due to the glossy and smooth nature of a dental material that has been properly glazed .…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have shown that mechanical polishing can restore the ceramic smoothness to a level close to that of the glazed ceramics . However, other studies have shown that the best procedure is glazing . In fact, the quality of ceramic or composite resin polishing methods is a controversial topic in the literature.…”
Section: Introductionmentioning
confidence: 99%